Chronic Administration of the Nitroxyl Donor 1-Nitrosocyclo Hexyl Acetate Limits Left Ventricular Diastolic Dysfunction in a Mouse Model of Diabetes Mellitus In Vivo. (May 2015) - Cao, Nga; Wong, Yung George; Rosli, Sarah; Kiriazis, Helen; Huynh, Karina; Qin, Chengxue; Du, Xiao-Jun; Kemp-Harper, Barbara K.; Ritchie, Rebecca H.
<x xml:space="preserve">Abstract</x> Background— Nitroxyl (HNO), a redox congener of nitric oxide (NO·), is a novel regulator of cardiovascular function, combining concomitant positive inotropic, lusitropic, and vasodilator properties. Moreover, HNO exhibits myocardial antihypertrophic and superoxide-suppressing actions. Despite these favorable actions, the impact of chronic HNO administration has yet to be reported in the context of cardiomyopathy. Diabetic cardiomyopathy is characterized by early diastolic dysfunction and adverse left ventricular (LV) structural remodeling, with LV superoxide generation playing a major causal role. We tested the hypothesis that the HNO donor 1-nitrosocyclohexylacetate (1-NCA) limits cardiomyocyte hypertrophy and LV diastolic dysfunction in a mouse model of diabetes mellitus in vivo. Methods and Results— Diabetes mellitus was induced in male FVB/N mice using streptozotocin. After 4 weeks, diabetic and nondiabetic mice were allocated to 1-NCA therapy (83 mg/kg per day IP) or vehicle and followed up for a further 4 weeks. Diabetes mellitus–induced LV diastolic dysfunction was evident on echocardiography-derived E and A wave velocities, E:A ratio, deceleration, and isovolumic relaxation times; LV systolic function was preserved. Increased LV cardiomyocyte size, hypertrophic and profibrotic gene expression, and upregulation of LV superoxide were also evident. These characteristics of diabetic cardiomyopathy were largely prevented by 1-NCA treatment. Selectivity of 1-NCA as an HNO donor was demonstrated by sensitivity of acute 1-NCA to L-cysteine but not to hydroxocobalamin in the normal rat heart ex vivo. Conclusions— Our studies provide the first evidence that HNO donors may represent a promising strategy for treatment of diabetic cardiomyopathy and implies therapeutic efficacy in settings of chronic heart failure.